2019
DOI: 10.1007/s11417-019-09289-w
|View full text |Cite
|
Sign up to set email alerts
|

Blurring the Distinction Between Empirical and Normative Legitimacy? A Methodological Commentary on ‘Police Legitimacy and Citizen Cooperation in China’

Abstract: In a fascinating study into the nature of police legitimacy in Southern China, Sun et al. (2018) present evidence that what researchers have previously been treated as possible sources of legitimacy-public perceptions of police conduct defined along the lines of procedural justice, distributive justice, effectiveness and lawfulness-are in fact constituent components of legitimacy. In this methodological commentary, we argue that the empirical strategy used to reach this conclusion is not fit for purpose becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 51 publications
2
71
0
9
Order By: Relevance
“…Our examination of which aspects of PJT translate-and which do notcontributes to the growing international literature on instrumental and normative police-citizen relations (Sunshine & Tyler, 2003;Papachristos et al, 2012;Tyler & Jackson, 2014;Murphy et al, 2016;Trinkner et al, 2018). Our findings also add to ongoing debate about the meaning, measurement, sources and consequences of legitimacy (Tyler, 2006a(Tyler, , 2006bReisig et al, 2007;Jackson et al, 2012;Bottoms & Tankebe, 2012;Jackson & Gau, 2015;Hamm et al, 2017;Jackson & Bradford, 2019;Posch et al, 2020).…”
supporting
confidence: 55%
See 2 more Smart Citations
“…Our examination of which aspects of PJT translate-and which do notcontributes to the growing international literature on instrumental and normative police-citizen relations (Sunshine & Tyler, 2003;Papachristos et al, 2012;Tyler & Jackson, 2014;Murphy et al, 2016;Trinkner et al, 2018). Our findings also add to ongoing debate about the meaning, measurement, sources and consequences of legitimacy (Tyler, 2006a(Tyler, , 2006bReisig et al, 2007;Jackson et al, 2012;Bottoms & Tankebe, 2012;Jackson & Gau, 2015;Hamm et al, 2017;Jackson & Bradford, 2019;Posch et al, 2020).…”
supporting
confidence: 55%
“…If, for example, procedural justice is a strong positive predictor of normative alignment, then we infer from this is an important dimension of appropriate (i.e. legitimate) police conduct-it is, we infer, a key element that defines what exercising authority in appropriate ways means in practice (for discussion, see Huq et al, 2017;Jackson & Bradford, 2019;. We turn to duty to obey in study two.…”
Section: Data Measures and Analytical Strategymentioning
confidence: 92%
See 1 more Smart Citation
“…Because of legitimacy, people feel that they ought to defer to decisions and rules, following them voluntarily out of obligation rather than out of fear of punishment or anticipation of reward.' At the operational level, researchers have measured legitimacy in a variety of different ways (for discussion, see Reisig et al, 2007;Hawdon, 2008;Bottoms & Tankebe, 2012;Tyler & Jackson, 2013;Jackson & Gau, 2015;Hamm et al, 2017;Jackson, 2018;Jackson & Bradford, 2019;Trinkner, 2019;Posch et al, forthcoming). One approach has been to use a single indicator of trust or confidence in the police as a proxy for legitimacy (e.g.…”
Section: Why Do People Cooperate With the Police?mentioning
confidence: 99%
“…This special issue contains the first article titled "Blurring the Distinction Between Empirical and Normative Legitimacy? A Methodological Commentary on 'Police Legitimacy and Citizen Cooperation in China'" by Jackson and Bradford (2019) which is aimed at making a methodological commentary to the paper of Sun et al (2018). This commentary indicated that Sun and his colleagues blurred the distinction between empirical and normative legitimacy at the conceptual aspect and overly interpreted the statistical analysis result at the methodological aspect, which meant that confirmatory factor analysis could not decide the four aspects (procedural justice, distributive justice, effectiveness, and lawfulness) as the source or the constituent components of police legitimacy.…”
mentioning
confidence: 99%